DYNAMICS OF SOCIAL REPRESENTATIONS AND COLLECTIVE IDENTITY OF UKRAINIANS (2010–2025): A COMPARATIVE SOCIO-PSYCHOLOGICAL ANALYSIS - Prokopenko, Vadym (PSYCHOLOGICAL JOURNAL, 2026)
The article examines the transformation of social representations and collective identity in Ukrainian society during the period from 2010 to 2025 under conditions of political instability, war, and radical sociocultural change. The relevance of the study is determined by the need for a socio-psychological understanding of the processes of consolidation of the Ukrainian political nation, changes in the structure of collective consciousness, and the reorientation of social behavior patterns under prolonged existential threat. Particular attention is paid to the analysis of the dynamics of the collective “We-image,” locus of control, transformation of paternalistic attitudes, and the formation of the phenomenon of “defensive subjectivity.” The methodological framework of the study is based on the theory of social representations, concepts of collective trauma, posttraumatic growth, resilience, and social identity. The research employs a comparative analytical and theoretical approach combined with a secondary analysis of longitudinal sociological monitoring data obtained from the Institute of Sociology of the National Academy of Sciences of Ukraine, the Razumkov Centre, the Kyiv International Institute of Sociology, and the Sociological Group “Rating.” The study analyzes transformations in civic, regional, and geopolitical identities, levels of trust, social distance, resilience, and attitudes toward Euro-Atlantic integration. The findings demonstrate a fundamental transformation of Ukrainian collective consciousness — from a state of post-Soviet apathy and external locus of control to a model of mobilizational subjectivity and strong civic consolidation. It was established that the events of 2014–2025 became catalysts for posttraumatic growth, the development of an internal locus of control, and the reinterpretation of the state as a space of collective responsibility. The study identified a significant increase in civic identity, a reduction in regional fragmentation, and the near disappearance of Soviet identity as a social phenomenon. The phenomenon of the “paradox of subjectivity” was conceptualized as a combination of strong symbolic national subjectivity with an awareness of economic and security dependence on external partners. The research also revealed risks of emotional exhaustion, the emergence of “adaptive alienation,” and the transformation of paternalism into a form of “wartime paternalism.” The obtained results deepen the understanding of socio-psychological mechanisms underlying the formation of national resilience during prolonged military conflict and may be applied in forecasting further transformations of Ukrainian society. Keywords: social representations; collective identity; civic identity; resilience; locus of control; posttraumatic growth; social distance; subjectivity; wartime paternalism; Ukrainian society; social psychology. Received: December 23, 2025 Accepted: February 20, 2026 Published: March 30, 2026